ANALISIS HUKUM KONTRAK JUAL BELI ONLINE DALAM PERSPEKTIF PERLINDUNGAN KONSUMEN - Manangin, Susi Aryani (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This study aims to analyze consumer protection in online buying and selling transactions from a legal perspective, with a focus on the implementation of electronic contracts in Indonesia. In the era of e-commerce that continues to evolve rapidly, it is important to understand the legal protection mechanisms that can overcome challenges in online transactions, such as fraud and unclear product information. The research method used is a normative juridical approach with literature studies that include laws and regulations, legal documents, and analysis of various case studies related to online sales contracts. The results of the study show that although there have been several regulations regulating electronic contracts and consumer protection, the application of the law in practice still encounters various obstacles. Weak oversight and a lack of consumer understanding of their rights are major challenges. Other findings show that online sales and purchase contracts must comply with the provisions of the validity of the agreement based on the Civil Code. At the same time, the Consumer Protection Law and the ITE Law provide a strong legal basis for the protection of consumer rights. However, law enforcement still needs to be improved, especially regarding the anonymity of perpetrators and the diversity of international law. This research also highlights the importance of the role of the National Police in handling online buying and selling cases and consumer protection through prevention, investigation, and stricter law enforcement. Overall, this study suggests that the government should strengthen regulations and increase education to consumers to create a safe and reliable e-commerce ecosystem